The Pathophysiology and Care of Exercise Related Muscle Cramps - Abhay Kumar Pandey; Abha Pandit; B L Pandey (Journal of Tropical Life Science, 2015)
Cramps are major concerns to competing athletes. The pain alone is not object of treatment as serious metabolic disturbance of electrolyte must gets due consideration. The phenomenon is dealt with some patho-physiological details and relevant clinical information, important as first hand understanding for the sports persons and their care givers.